Ruqyah as a Religious Coping Practice: Healing Communication and Meaning- Making in Contemporary Islam - Hilmi Mubarok; Muhamad Hanif Fuadi (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Faith-based healing practices continue to play an important role in the way Muslims interpret the experience of illness amid the evolving modern health system. Ruqyah is often understood as a spiritual ritual or religious intervention, while its role as a practice of communicating meaning is still poorly explored. This article examines ruqyah as a form of religious coping that functions through healing communication in the context of contemporary Islam. Using a qualitative approach based on literature review, this study analyzes scientific works on religious coping, Islamic spiritual healing, and the relationship between religion and modernity. The analysis shows that ruqyah operates not only as a spiritual practice, but also as a symbolic mechanism that helps individuals establish meaning, hope, and acceptance of the experience of pain. These findings affirm the importance of religious communication in maintaining the process of meaning and strengthening the relevance of Islamic practices in the midst of an increasingly medicalized social environment. This article contributes to the study of Islamic Studies by expanding the understanding of religious coping through the perspective of meaning communication, which has received less attention in ruqyah studies. This research offers a new contribution by conceptualizing ruqyah not only as a ritual or therapy, but as a process of creating communicative meaning in the theory of religious coping.